High-Sensitivity Troponin T: A Biomarker for Diuretic Response in Decompensated Heart Failure Patients - João Pedro Ferreira; Mário Santos; Sofia Almeida; Irene Marques; Paulo Bettencourt; Henrique Carvalho (Cardiology Research and Practice)
Background. Patients presenting with acutely decompensated heart failure (ADHF) and positive circulating cardiac troponins were found to be a high-risk cohort. The advent of high-sensitive troponins resulted in a detection of positive troponins in a great proportion of heart failure patients. However, the pathophysiological significance of this phenomenon is not completely clear. Objectives. The aim of this study is to determine the early evolution and clinical significance of high-sensitivity troponin T (hsTnT) in ADHF. Methods. Retrospective, secondary analysis of a prospective study including 100 patients with ADHF. Results. Globally, high-sensitivity troponin T decreased from day 1 to day 3 (P=0,039). However, in the subgroup of patients who remained decompensated no significant differences in hsTnT from day 1 to day 3 were observed (P=0,955), whereas in successfully compensated patients a significant reduction in hsTnT levels was observed (P=0,025). High-sensitivity troponin T decrease was correlated with NTproBNP reduction (P=0,007). Patients with hsTnT increase had longer length of stay (P=0,033). Conclusions. Episodes of ADHF are associated with transient increases in the blood levels of hsTnT that are reduced with effective acute episode treatment. The decrease in hsTnT can translate less myocardial damage along with favourable ADHF treatment.